The Intersectionality and Human Rights: A Bioethical Approach - Zambrano, Yuri (2024)
Intersectionality is a tool of analysis based primarily on the specific identification of social inequalities and the possibility of confronting their injustices in the field of human rights. Such inequalities generate a multidimensional spectrum whose line of categorisation is viewed through the lens of classical concepts of domination. This article discusses four salient elements of intersectionality in philosophy of law: a) its general background, b) the ideology of domination and the philosophical approach to power, c) the relation of oppression to elements of human rights such as discrimination in cases of race, disability, ethnicity and nation, gender, education, social class, religion, age and sex and, finally, d) some bioethical-legal considerations directed towards an updated state of the art.